Asymptotic methods applied to the correlation of fretting fatigue lives - Hills,DA; Churchman,CM; Dini,D (Proceedings of the World Tribology Congress III 2005, 2005)
Local or asymptotic states of stress relevant to the characterization of the state of stress adjacent to the edges of incomplete contacts are discussed. It is shown that the multipliers for the asymptotic solutions effectively characterize the nucleation propensity of the geometries. This idea is tested by applying the approach to reliable fretting fatigue data in the literature, and re-examining it in this light. Copyright © 2005 by ASME.